Pengaruh Kerjasama Tim dan Motivasi Kerja terhadap Kinerja Karyawan PT Amythas Jakarta Selatan - Rahmat Ardiansyah; Purwatiningsih Purwatiningsih; Ratih Setyo Rini (Global Leadership Organizational Research in Management, 2024)
The aim of this research is to determine the influence of teamwork and work motivation on employee performance at PT Amythas South Jakarta. This research was carried out in April-June. In this research the author used quantitative research methods. Data collection uses observation, questionnaires and documentation methods. with a sample size of 60 people. The research results concluded that there was a partially significant influence between teamwork on employee performance, proven based on the results of the t test or partial test with a probability value of 0.001 < 0.05 and a calculated t value > t table of 7.939 > 2.001. There is a partially significant influence between work motivation and employee performance, proven based on the results of the t test or partial test with a probability value of 0.001 < 0.05 and a calculated t value > t table of 10.666 > 2.001. There is a significant simultaneous influence between teamwork and work motivation on employee performance at PT Amythas South Jakarta, proven based on the results of the F test or simultaneous testing with a probability value of 0.001 < 0.05 and a calculated F value > F table, namely 58.576 > 3 .16.